Changes in health‐related quality of life in older candidates waiting for kidney transplantation. Issue 10 (24th September 2018) - Lønning, Kjersti; Midtvedt, Karsten; Bernklev, Tomm; Brunborg, Cathrine; Andersen, Marit H; von der Lippe, Nanna; Reisæter, Anna V; Line, Pål‐Dag; Hartmann, Anders; Heldal, Kristian
Summary at a Glance: In a cohort of 261 elderly Norwegian patients with CKD stage 5 accepted for transplant, health‐related quality of life decreased modestly during the first year on the waiting list. This study provides some reassurance that selected elderly transplant candidates maintain reasonable quality of life while awaiting deceased donor kidney transplantation. ABSTRACT: Aim: There is limited available knowledge regarding health‐related quality of life (HRQoL) in older patients with chronic kidney disease. We aimed to describe HRQoL in renal transplant candidates 65 years or older at transplant acceptance, and during the first year on the waiting list. Methods: A nationwide prospective observational study in Norway was conducted. HRQoL was evaluated at baseline (wait listing) and after 6 and 12 months using the patient self‐reported Kidney Disease and Quality of Life Short form version 1.3. Intra‐individual scores at different times were evaluated. Generic HRQoL was compared with scores from an age‐matched Norwegian population. Results: From January 2013 to November 2016, 261 patients ≥65 years accepted for deceased donor kidney transplantation were included. Mean age at inclusion was 71.1 years, 67% male and 69% were on dialysis. HRQoL sum scores significantly decreased during the first year on the waiting list. Physical, mental and kidney disease component summary score reduced from 39.6 to 38.1 ( P =  0.045), 48.8 to 44.7 ( P <  0.001) and 72.1 to 70.2 ( P =  0.03), respectively. When evaluating each domain separately, only the decrease in social function was clinically significant. Age and being on dialysis were the most important predictors for low HRQoL. Compared to the age‐matched general population, males had significant lower HRQoL scores. Females were comparable to the general female population at baseline except in general health and vitality. Conclusions: HRQoL in older patients waiting for kidney transplantation decreases during the first year on the waiting list, but only the change in social function is clinically significant.